Nanoformulação do óleo essencial de alecrim-pimenta (Lippia sidoides) na ensilagem de milho (Zea mays L.) - Cerqueira, Alan Silva (2018)
The objective of this work was to study the effects of the essential oil of Lippia sidoides, nanoformulated (OEN), on microbiological counts, chemical composition, fermentative losses and aerobic stability of corn silage. The experiment was conducted at the experimental farm (Campus Rural) of the Federal University of Sergipe (UFS), located in the municipality of São Cristovão / SE, Brazil. The design was completely randomized in a 4x3 factorial scheme with five replications. The treatments were composed of four levels of essential oil addition of lippia sidoides nanoformulated (0, 100, 400 and 700 mg kg-1) in the natural material (MN) and three silage opening times (15, 30 and 45 days after closure of the silo). Sixty experimental mini silos were used, totaling 12 treatments with five replicates. The addition of 700 mg kg-1 of OEN reduces the development of Clostridium, fungi, yeast and controls the development of enterobacteria in the early days of silage, also reduces the level of effluents reducing nutrient leaching. For fungi and yeast, the level of 700 mg kg-1 was also the one that showed better responses in relation to the control, inhibiting their growth with a minimum reduction of 0.9 log ufc g-1. It was not observed the effect of the inclusion of OEN in the chemical composition, making evident the capacity of the oil in the conservation of the chemical components of the forage after the fermentation process. The aerobic stability was not directly influenced by the OEN addition, but showed a significant difference (P <0.05) for the variables accumulated temperature and maximum temperature as a function of the days of opening. The essential oil of Lippia sidoides nanoformulated presents potential as an alternative to the use of additives in corn silage, however more studies are needed.